Perbedaan Pola Hubungan antara Orang Tua dan Anak Usia Dini Ditinjau dari Tingkat Stres Pengasuhan pada Masa Pandemi Covid-19 - Nur Fatwikiningsih; Lathifatul Fajriyah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
The COVID-19 pandemic impacting the family dynamics, one of which is parenting stress take care of their early childhood. This study aimed to investigate the pattern of parent-child relationships during early childhood and the levels of parenting stress during the COVID-19 pandemic. The research sample was determined by random sampling. A sample consists of 53 fathers and 92 mothers who have sons or daughters attending school in one of 36 PAUD institutions inthe Gresik District. Child parent relationship scale (CPRS) and Parental Stress Scale (PSS) were administered to 145 parents via the Google Form separately for the Mother and Father. Child parent relationship scale (CPRS) to measure parent-child relationship patterns and Parental Stress Scale(PSS) to measure the levels of parenting stress. Results withchi-square analysisfound parenting stress impact on the pattern of parent-child relationships during early childhood significantly value is less than 0.05 (0,000 <0.05). Also, there is a significant difference in the pattern of mother-child relationships during early childhood in terms of parental stress levels during the COVID-19 pandemic (significance value less than 0.05 or 0.003 <0.05) but not significantly for father-child relationships (significance value over from 0.05 or 0.081> 0.05)